2022
DOI: 10.3389/fnut.2022.952056
|View full text |Cite
|
Sign up to set email alerts
|

Iron metabolism mediates the relationship between Vitamin C and hepatic steatosis and fibrosis in NAFLD

Abstract: Vitamin C (Vit C) and iron metabolism are closely related to metabolic disorders. However, the relation between iron storage protein ferritin and Vit C has not been elucidated. We aimed to investigate the crosstalk between Vit C and ferritin and its implications on non-alcoholic fatty liver disease (NAFLD). Clinical information of 3,614 subjects was obtained from the NHANES Public Data 2017–2018. FibroScan data, which estimates liver steatosis and fibrosis and Vit C, were selected to assess factors influencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…Vitamin C and vitamin E, also known as ascorbic acid and tocopherol, respectively, play significant roles in the redox system because of their excellent antioxidant activity. Abundant epidemiologic evidence has demonstrated that a high vitamin C intake level is a protective factor for MAFLD [182][183][184]. Vitamin C deficiency increases hepatic steatosis, oxidative stress, fibrosis, and inflammation, which is an important potential pathogenic factor of MAFLD [185].…”
Section: Vitamin C and Vitamin E Metabolism And Mafldmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin C and vitamin E, also known as ascorbic acid and tocopherol, respectively, play significant roles in the redox system because of their excellent antioxidant activity. Abundant epidemiologic evidence has demonstrated that a high vitamin C intake level is a protective factor for MAFLD [182][183][184]. Vitamin C deficiency increases hepatic steatosis, oxidative stress, fibrosis, and inflammation, which is an important potential pathogenic factor of MAFLD [185].…”
Section: Vitamin C and Vitamin E Metabolism And Mafldmentioning
confidence: 99%
“…However, there is also evidence that chronic vitamin C deficiency impairs SREBP1c activation, thereby inhibiting hepatic de novo lipogenesis and suppressing MAFLD progression [190]. Notably, vitamin C also plays an important role in maintaining iron homeostasis and is strongly associated with MAFLD [184]. This reflects the crosstalk between vitamins and minerals.…”
Section: Vitamin C and Vitamin E Metabolism And Mafldmentioning
confidence: 99%
“…Повышенный ферритин сыворотки был фактором риска НАЖБП, а повышенный уровень витамина С, напротив, был защитным фактором от НАЖБП и фиброза печени. Эксперименты на гепатоцитах линии hepG2 показали, что витамин C облегчает стеатоз и поддерживает гомеостаз железа за счет ингибирования повышения ферритина и пула лабильного железа [18]. Концентрации железа в сыворотке крови были обратно пропорциональны риску НАЖБП при прогрессирующем фиброзе печени (P = 0.018) [19].…”
Section: клинические последствия нажбп ассоциированные с перегрузкой ...unclassified
“…To maintain the balance of the mitochondrial oxidation reaction, mitochondria have antioxidation enzymes and antioxidant molecules (glutathione, VE, etc.) to eliminate mt-ROS accumulation by capturing and removing free radicals and harmful substances to repair oxidative damage [83]. Recently, it has been found that the nuclear factor-κB (NF-κB) pathway has bidirectional effects in different stages of the oxidative stress response in the pathogenesis of MAFLD [84].…”
Section: Oxidative Phosphorylationmentioning
confidence: 99%
“…According to its antioxidant properties, VC plays an important role in scavenging oxygen free radicals. The basic mechanism by which VC alleviates the degree of oxidative stress is through reducing the generation of mt-ROS and increasing the levels of antioxidant enzymes such as superoxide dismutase and GSH peroxidase, thereby improving the activity of the ETC [83]. At the same time, VC inhibits fat accumulation by activating PPARα in MAFLD.…”
Section: Vitamin Cmentioning
confidence: 99%